Combination therapy with zidovudine and didanosine selects for drug-resistant human immunodeficiency virus type 1 strains with unique patterns of pol gene mutations. - Shafer, R; Kozal, M; Winters, M; Iversen, A; Katzenstein, D; Ragni, M; Meyer, W; Gupta, P; Rasheed, S; Coombs, R (1994)
Drug resistance conferred by specific human immunodeficiency virus type 1 (HIV-1) pol gene mutations has been associated with clinical progression in HIV-infected patients receiving anti-retroviral therapy. This study examined drug susceptibilities and pol mutations of HIV-1 strains from patients treated for 1 year with zidovudine, didanosine (ddI), or zidovudine and ddI. Ten (42%) of 24 patients receiving combination therapy versus 8/26 (31%) receiving only zidovudine had HIV-1 strains with phenotypic zidovudine resistance or a zidovudine resistance pol mutation at codon 215 (P = .6). In contrast, a ddI resistance mutation at codon 74 was less common among patients receiving combination therapy (2/24) than among those receiving ddI only (17/26; P < .001). Two patients receiving combination therapy developed resistance to zidovudine and ddI; they had HIV strains with amino acid mutations at codons 62, 75, 77, 116, and 151. Combination therapy with zidovudine and ddI selects for zidovudine-resistant HIV-1 strains lacking a ddI resistance mutation and for multidrug-resistant strains containing novel pol mutations.